The THE IMPACT OF PSYCHOLOGICAL DEVELOPMENT THROUGH READING ACTIVITY BOOKS BASED ON EDUCATIONAL NEUROSCIENCE ON CHILDREN AGED 4-6 YEARS IN SERANG BARU DISTRICT, BEKASI REGENCY - alkehfi rakhmawati (Universitas Panca Sakti Bekasi, 2023)
This study aims to analyze the impact of psychological development through reading activity books based on educational neuroscience in children aged 4-6 years in Serang Baru District, Bekasi Regency. The research used is qualitative research. The type of approach used is a qualitative descriptive approach. Data collection techniques are observation, interviews, and documentation. The data collection instruments used were observation sheets and interviews. Data validity test: using several data sources or data collection methods to compare and match findings (triangulation). The data analysis process is as follows: data transcript, referring to the problem formulation, coding process, clustering, thematic labeling, and interpretation. The results of the study found that stimulation of reading educational neuroscience activity books had an impact on the psychological development of children aged 4-6 years. Elements of identity that emerge include types of emotion, social perception, and the ability to empathize that arise from children's behavior after receiving stimulation from an educational neuroscience activity book entitled